Demotion from a sustainable career perspective: A review of the antecedents and consequences of demotion in human resource management - Remzi Gürer Gerçek; Merve Gerçek (Trakya Üniversitesi İktisadi ve İdari Bilimler Fakültesi E-Dergi)
Demotion, defined as a reduction in rank, responsibilities, salary, and benefits, is often viewed as a taboo within organizations, yet it presents significant challenges for human resource management. This study provides a comprehensive analysis of demotion, exploring its antecedents and consequences while offering recommendations for addressing it through a sustainable career approach. A systematic review of existing literature on demotion identifies theoretical frameworks and research methodologies, establishing a framework for the current state of knowledge based on key findings. Results indicate that demotion decisions are influenced by environmental, organizational, and individual factors, resulting in diverse reactions from employees based on these aspects. Involuntary demotion often results in negative outcomes related to organizational justice and psychological contracts. Conversely, voluntary demotion can improve employees' work-life balance or create new career opportunities. This research aims to serve as a valuable resource for managers, human resource specialists, work and organizational psychologists, and researchers in both public and private sectors, providing insights into the complexities of demotion in organizational contexts.